2014
DOI: 10.3109/03009742.2014.922214
|View full text |Cite
|
Sign up to set email alerts
|

The influence of therapy on CD4+CD25highFOXP3+ regulatory T cells in systemic lupus erythematosus patients: a prospective study

Abstract: Increase in Tregs during SLE remission is independent of the therapeutic regimen used and probably represents an epiphenomenon of disease remission. Time to Tregs restoration was significantly shorter in patients treated with iv MP and IVIGs compared to CYP pulse therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The present study supports the results of prior studies regarding improvement in the levels of circulating Treg cells following disease remission . This improvement in Treg frequency was seen as early as 3 months in the responder group, even though it showed a mild non‐significant decline after 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…The present study supports the results of prior studies regarding improvement in the levels of circulating Treg cells following disease remission . This improvement in Treg frequency was seen as early as 3 months in the responder group, even though it showed a mild non‐significant decline after 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…Most current treatments are unsuccessful in stopping disease reoccurrence after remission and may have unacceptable side effects after long-term use [11]. Although the mechanism is not understood, Tregs have been seen to modestly increase with the use of drugs not targeting Tregs, such as pyridostigmine, rituximab, azathioprine, and IVIG [190193]. Corticosteroids lack specificity and importantly cause severe adverse effects such as bruising, abnormal weight gain, behavior changes, oral thrush, and others [194].…”
Section: Main Textmentioning
confidence: 99%
“…These results are in line with numerous published reports showing an imbalance between Treg cells and effector T cells in active SLE [ 11 , 12 ]. Numerous studies have also shown that the number of Treg cells returns to normal values when the disease is inactive [ 5 , 10 , 13 ]. Therefore, the manipulation of Treg cells to increase their number is considered an interesting potential therapeutic strategy to develop in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the induction of Treg cells may contribute to the immunosuppressive effects of glucocorticoids [ 24 28 ]. In SLE, a slight increase in the proportion of circulating Treg cells has been reported in patients taking oral prednisone [ 29 31 ]; the time to Treg cell recovery was reduced in patients treated with IV high dose MP [ 13 ]. However, to our knowledge, there has been no detailed report on the short-term effects of IV high dose MP on the different subsets of FoxP3 + T cells in active SLE until now.…”
Section: Introductionmentioning
confidence: 99%